2021
DOI: 10.3390/jpm11030166
|View full text |Cite
|
Sign up to set email alerts
|

ADHD: Reviewing the Causes and Evaluating Solutions

Abstract: Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder in which patients present inattention, hyperactivity, and impulsivity. The etiology of this condition is diverse, including environmental factors and the presence of variants of some genes. However, a great diversity exists among patients regarding the presence of these ADHD-associated factors. Moreover, there are variations in the reported neurophysiological correlates of ADHD. ADHD is often treated pharmacologically, producing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 205 publications
(145 reference statements)
0
38
0
2
Order By: Relevance
“…This can lead to heightened hyperactivity and even in adulthood can lead to antisocial emotions and behaviors that increase crime rates. (3) Environmental factors: in the family environment of children with ADHD, a case-control study has shown that the results show that parents' low educational level and poor family discord and intimacy are important reasons for the bad behavior of ADHD children [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to heightened hyperactivity and even in adulthood can lead to antisocial emotions and behaviors that increase crime rates. (3) Environmental factors: in the family environment of children with ADHD, a case-control study has shown that the results show that parents' low educational level and poor family discord and intimacy are important reasons for the bad behavior of ADHD children [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, early interventions in children are essential, in order to reduce the repercussions in adolescence and adulthood. Among the effective treatments available for ADHD, the main differences are related to the type of intervention (pharmacological and non-pharmacological), the age of the patient, the cost, the available patient and caregiver time, the expected effectiveness in the reduction of symptoms, the adverse effects, safety, and tolerability [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although ADHD is often considered as a childhood disorder, it is reported that 50% of the symptoms continue during adolescence and 30–60% extend into adulthood and continue to meet the diagnostic criteria in adulthood (Ahmed et al, 2014 ). It has been suggested that the number of adults with ADHD has increased over the past 20 years, and some of this increase is explained by the persistence of ADHD symptoms in adulthood (Núñez-Jaramillo et al, 2021 ). As developmental brain processes alleviate some of the consequences of ADHD with neural normalization, the symptoms of hyperactivity disappear wherever they are in adulthood, but the persistence of the symptoms of inattention from childhood to adulthood is emphasized (Duan et al, 2021 ).…”
mentioning
confidence: 99%
“…In addition to epidemiological and clinical studies, mechanistic evidence has been obtained from animal models consistent with the behavioral and neural consequences of maternal immune activation with ADHD (Dunn et al, 2019 ). It has been reported that neurodevelopmental high inflammatory responses by a number of mechanisms such as exposure to heavy metals, preterm birth, and perinatal problems such as nutrition or environmental factors may increase the risk of ADHD by conditional triggering evidence during perinatal development (Núñez-Jaramillo et al, 2021 ).…”
mentioning
confidence: 99%